Grammatical Mistakes in Relation to English Competency Test - Sosiowati, I Gusti Ayu Gde; Indrawati, Ni Luh Ketut Mas; Sukarini, Ni Wayan; Puspani, Ida Ayu Made (Lingual Journal of Language and Culture, 2016)
The research aims at finding out the freshmen’s ability on English grammar. This is very important activity so that the English department knows their level of ability so that the teaching materials can be determined. The test is about structure, taken from TOEFL. The theory used is the theory English Language Teaching, especially Testing by Harmer (2001), in which the test is used as diagnostic test. The result of the test will provide the information about three crucial points on grammar that must be developed. This will help the related teacher to decide what items should be taught so that by the end of the semester, at least most of the students can reach the level of Intermediate, that is the level in which the students are capable of doing conversations on routines, understanding lectures, understanding English TV programs (http://www.embassyenglish.com/student-life/your-level-of-english cited on 19 January 2015).
Keywords: testing; gramatical; intermediate